Strategies used to address challenges encountered during website development in South Africa - Josephine R. Chivinge (AOSIS, 2021)
Background: Whether a website design is a simple static page of plain text, a complex e-commerce matrix or a progressive web application, the journey is riddled with challenges. In terms of online users, every second counts when interacting with a website. It is estimated that 2 seconds is the acceptable webpage loading latency that users are willing to tolerate before abandoning a webpage. Users expect web applications to be more usable, reliable, secure, personalised and context-aware.